2003
DOI: 10.1007/bf02443639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca2+ on the self assembly of a nonionic peptide aggregate

Abstract: SummaryConductometry, circular dichroism and fluorescence spectroscopy are the techniques employed to investigate the effect of added calcium ions and other monovalent and divalent metal ions on aqueous solutions of nonionic peptide aggregates, Boc-Leu-Asn-OEt (1). It is observed that among all the metal ions studied, Ca 2+ ions facilitate the aggregation of the peptide. The interior dielectric constant of the micelles (z) was found to depend upon the proportion of Ca 2+ complexed peptide with the peptide mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In industrial practice, salts have frequently played an important role in controlling the viscosity and the on-surface functionalities of polyelectrolytes such as carbohydrate and cellulose . Previous studies have shown that divalent counterions can lead to a surface charge reversal of a negatively charged solid surface, , while for bulk macromolecular solution, it has been demonstrated that they can induce aggregation or precipitation of charged surfactants and proteins by screening the electrostatic repulsion . Although divalent ions have commonly been added to solutions to help the polyelectrolyte adsorb to solid surfaces, , for example in the application of lime to soil clay and EDTA on glassware cleaning, most studies on their effect of modulating the forces and interactions between charged polymers and surfaces are indirect, relying on theoretical simulations or observations made with scanning microscopy. ,,, There were only a few direct force measurements in which only the counterion valency is varied. , Recently more in-depth studies have started to focus on a more simplified model system of polyelectrolytes at solid surfaces, seeking experimental support for the predicted attraction mediated by divalent ions. , Interestingly, it has been realized that the divalent counterions’ role could be more than just enhancing the adsorption of charged polyelectrolyte at similarly charged surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In industrial practice, salts have frequently played an important role in controlling the viscosity and the on-surface functionalities of polyelectrolytes such as carbohydrate and cellulose . Previous studies have shown that divalent counterions can lead to a surface charge reversal of a negatively charged solid surface, , while for bulk macromolecular solution, it has been demonstrated that they can induce aggregation or precipitation of charged surfactants and proteins by screening the electrostatic repulsion . Although divalent ions have commonly been added to solutions to help the polyelectrolyte adsorb to solid surfaces, , for example in the application of lime to soil clay and EDTA on glassware cleaning, most studies on their effect of modulating the forces and interactions between charged polymers and surfaces are indirect, relying on theoretical simulations or observations made with scanning microscopy. ,,, There were only a few direct force measurements in which only the counterion valency is varied. , Recently more in-depth studies have started to focus on a more simplified model system of polyelectrolytes at solid surfaces, seeking experimental support for the predicted attraction mediated by divalent ions. , Interestingly, it has been realized that the divalent counterions’ role could be more than just enhancing the adsorption of charged polyelectrolyte at similarly charged surfaces.…”
Section: Introductionmentioning
confidence: 99%